At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To find the value of the expression [tex]\(2a^2 + 5b^2\)[/tex] when [tex]\(a = -6\)[/tex] and [tex]\(b = 2\)[/tex], follow these steps:
1. Substitute the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
- [tex]\(a = -6\)[/tex]
- [tex]\(b = 2\)[/tex]
2. Square the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
- [tex]\(a^2 = (-6)^2 = 36\)[/tex]
- [tex]\(b^2 = (2)^2 = 4\)[/tex]
3. Multiply the squared values by their respective coefficients:
- [tex]\(2a^2 = 2 \cdot 36 = 72\)[/tex]
- [tex]\(5b^2 = 5 \cdot 4 = 20\)[/tex]
4. Add the results together:
- [tex]\(2a^2 + 5b^2 = 72 + 20 = 92\)[/tex]
So, the value of the expression [tex]\(2a^2 + 5b^2\)[/tex] when [tex]\(a = -6\)[/tex] and [tex]\(b = 2\)[/tex] is [tex]\(\boxed{92}\)[/tex].
1. Substitute the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
- [tex]\(a = -6\)[/tex]
- [tex]\(b = 2\)[/tex]
2. Square the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
- [tex]\(a^2 = (-6)^2 = 36\)[/tex]
- [tex]\(b^2 = (2)^2 = 4\)[/tex]
3. Multiply the squared values by their respective coefficients:
- [tex]\(2a^2 = 2 \cdot 36 = 72\)[/tex]
- [tex]\(5b^2 = 5 \cdot 4 = 20\)[/tex]
4. Add the results together:
- [tex]\(2a^2 + 5b^2 = 72 + 20 = 92\)[/tex]
So, the value of the expression [tex]\(2a^2 + 5b^2\)[/tex] when [tex]\(a = -6\)[/tex] and [tex]\(b = 2\)[/tex] is [tex]\(\boxed{92}\)[/tex].
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.